Correction of extrahepatic portal hypertension in pediatric patient after liver transplantation - A. R. Monakhov; B. L. Mironkov; T. A. Dzhanbekov; K. O. Semash; Kh. M. Khizroev; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2017)
Introduction. Liver transplantation is a multi-component and complex type of operative treatment. Patients undergoing such a treatment sometimes are getting various complications. One of these complications is a portal hypertension associated with portal vein stenosis.Materials and methods. In 6 years after the left lateral section transplantation from living donor in a pediatric patient the signs of portal hypertension were observed. Stenosis of the portal vein was revealed. Due to this fact percutaneous transhepatic correction of portal vein stenosis was performed.Results. As a result of the correction of portal blood flow in the patient a positive trend was noted. According to the laboratory and instrumental methods of examination the graft had a normal function, portal blood flow was adequate. In order to control the stent patency Doppler ultrasound and MSCT of the abdominal cavity with intravenous bolus contrasting were performed. Due to these examinations the stent function was good, the rate of blood flow in the portal vein due to Doppler data has reached 80 cm/sec, and a decrease of the spleen size was noted.Conclusion. Diagnosis and timely detection of portal vein stenosis in patients after liver transplantation are very important for the preservation of graft function and for the prevention of portal hypertension. In order to do that, ultrasound Doppler fluorimetry examination needs to be performed to each patient after liver transplantation. In cases of violation of the blood flow in the portal vein CT angiography performance is needed. Percutaneous transhepatic stenting of portal vein is a minimally invasive and highly effective method of correction of portal hypertension. Antiplatelet therapy and platelet aggregation control are the prerequisites for successful stent function.